(untitled) (Research, Society and Development, 2020)
This qualitative study aims to point out and discuss which characteristics of Mathematical Modeling are evidenced in the activities of the experience reports of the XI National Conference on Modeling in Mathematical Education (Conferência Nacional sobre Modelagem na Educação Matemática – CNMEM), developed in the context of the Elementary School. Data collection was performed by searching for experience reports on the XI CNMEM website. All experience reports published in the annals of the 11th edition of the conference that have as context the elementary school were selected. In this search, four articles were found, which constituted the corpus of the research. The analysis carried out is close to the process organized through open coding and data categorization, proposed by Flick. In the analytical process, five characteristics present in the work with Mathematical Modeling were evidenced, which are the results of the research, which were discussed separately in five categories that intertwined in the classroom experiences reported in the analyzed reports, named as follows: emergence of several contents in the same activity; challenges, difficulties and obstacles; discussion, mathematics and reflection; learning by doing; and leading the development of the activity.